Analisis Perbandingan Kinerja Keuangan Pemerintah dalam Pengelolaan Anggaran Pendapatan dan Belanja Daerah (APBD) Kota Bontang Tahun 2014-2018 - Sudarlan Sudarlan; Rahmawati Fitriana; Rezky Dayanti Mujiato (Politeknik Negeri Samarinda, 2022)
This study aims to determine the financial performance of local revenue of Bontang City for the period 2014-2018. Thw Analytical tools used are revenue growth, the degree of decentralization, regional independency, the regional financial dependency, the effectiveness of local taxes, and the degree of contribution of the BUMD contributions as well spending growth, operating expenditure, capital expenditure, and expenditure efficiency. The results showed that the financial performance of Bontang's regional income in general had increased. Even so the regional financial performance of the Bontang city in terms of revenue in general is still not good. This is evidenced by the average growth of income experiencing negative growth of -1.69%, the degree of decentralization ratio is still lacking due to a percentage of 13.37%, the ratio of regional independence is very low due to a percentage of 16.26%, the ratio of regional financial dependence is very high due to a percentage of 87.18%, the ratio of effectiveness of effective local tax due to a percentage of 107.55%, and the degree of contribution of BUMD has contributed due to the percentage of 3.23% and regional expenditure in the city of Bontang in general can be said to be good. This is evidenced by the average growth of expenditure experienced a negative growth of -2.02, the ratio of operating expenditure to total expenditure dominated because of a percentage of 71.15%, the ratio of capital expenditure to total expenditure did not dominate due to a percentage of 28.23%, and efficient shopping efficiency ratio due to a percentage of 84.87%.